2018
DOI: 10.1039/c7ce01910f
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing lithium-ion conductivity in NASICON glass-ceramics by adding yttria

Abstract: The lithium conductivity of NASICON glass-ceramic electrolytes can be increased 5 times just by using additives, which change the glass crystallization patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…In contrast, for sample LYGP‐C‐728, the overall room temperature conductivity is found to be two orders of magnitude higher than the reported one for the unsubstituted NASICON (LiGe 2 (PO 4 ) 3 ). A similarly surprising result was reported by Vizgalov et al who showed that the addition of Y 2 O 3 in the glass batch of Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 , resulted in the crystallization of YPO 4 upon thermal treatment. They also evidenced an increase in the ionic conductivity compared to the unsubstituted LGP NASICON phase and they attributed this enhancement to the presence of YPO 4 microcrystals, which promote better contact between the NASICON grains.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast, for sample LYGP‐C‐728, the overall room temperature conductivity is found to be two orders of magnitude higher than the reported one for the unsubstituted NASICON (LiGe 2 (PO 4 ) 3 ). A similarly surprising result was reported by Vizgalov et al who showed that the addition of Y 2 O 3 in the glass batch of Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 , resulted in the crystallization of YPO 4 upon thermal treatment. They also evidenced an increase in the ionic conductivity compared to the unsubstituted LGP NASICON phase and they attributed this enhancement to the presence of YPO 4 microcrystals, which promote better contact between the NASICON grains.…”
Section: Discussionsupporting
confidence: 68%
“…When substituting Na + with Li + , a NASICON-type lithium ion conductor can be acquired with a general formula of LiM 2 (PO 4 ) 3 (M = Ti, Ge, Hf, Zr, Sn). Like the LZP, the conductivity of the LTP and LGP is also on the order of 10 −5 -10 −6 S cm −1 , [76,77] far lower than the conductivity of liquid electrolytes (≈10 −2 S cm −1 ). [73] Similar to the Na 1+x Zr 2 Si x P 3−x O 12 , the ideal LZP has a rhombohedral structure, while Li atoms occupy Wyckoff positions of splitting 36f sites around 6b sites.…”
Section: Nasicon-type Ssesmentioning
confidence: 96%
“…The total ionic conductivity of polycrystalline NASICON-type lithium ion conductors is usually on the order of 10 −4 S cm −1 , while their bulk conductivity is considerably higher than 10 −4 S cm −1 . Compared with pristine conductors, notable enhancements have been described for Li-doped LAGP (1.9 × 10 −4 S cm −1 ), [85] B 2 O 3 -doped LAGP (6.9 × 10 −4 S cm −1 ), [86] Li 2 O-doped LAGP (7.25 × 10 −4 S cm −1 ), [87] SiO 2 -doped LATP (over 10 −3 S cm −1 ), [88] Y 2 O 3 -doped LAGP (5 × 10 −4 S cm −1 ), [77] and Bi 2 O 3 -doped LATP (9.4 × 10 −4 S cm −1 ). [83] M. Gellert et al [84] reported that the GB resistance was caused by a number of barriers.…”
Section: Garnet-type Ssesmentioning
confidence: 99%
See 1 more Smart Citation
“…It had a sandwiched structure with graphene working electrode, Li-conductive solid electrolyte and metallic Li counter electrode. Graphene was transferred from Cu foil onto a solid glass-ceramic NASICON-type electrolyte (Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 ) plate prepared in-house [36]. PMMAbased graphene transfer technique described elsewhere [37] was used.…”
Section: Photoemission Study Of the All-solid-state Li-o 2 Cellsmentioning
confidence: 99%